2014
DOI: 10.3389/fmars.2014.00047
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and population genetics of Eastern Mediterranean polychaetes

Abstract: Species and genetic diversity are often found to co-vary since they are influenced by external factors in similar ways. In this paper, we analyse the genetic differences of the abundant polychaete Hermodice carunculata (Pallas, 1766) during two successive years at two locations in northern Crete (Aegean Sea) and compare them to other populations in the Mediterranean Sea and the Atlantic Ocean. The genetic analysis is combined with an analysis of ecological divergence of the total polychaete community structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…We investigated the genetic diversity, effective number of migrants and population structure of H. carunculata populations collected from three regions: the Caribbean, the temperate eastern Atlantic (Tenerife of Canary Islands) and the eastern Mediterranean Sea (Malta and the Greek islands of Crete and Ikaria). Since samples were collected over a wide geographic range, we expected to find significant sequence divergence in H. carunculata as previously reported by Ahrens et al (2013) and Chatzigeorgiou et al (2014). Indeed, data from two mitochondrial markers indicated that there is a 2-2.5% divergence between the amphiatlantic populations of H. carunculata, confirming our expectations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We investigated the genetic diversity, effective number of migrants and population structure of H. carunculata populations collected from three regions: the Caribbean, the temperate eastern Atlantic (Tenerife of Canary Islands) and the eastern Mediterranean Sea (Malta and the Greek islands of Crete and Ikaria). Since samples were collected over a wide geographic range, we expected to find significant sequence divergence in H. carunculata as previously reported by Ahrens et al (2013) and Chatzigeorgiou et al (2014). Indeed, data from two mitochondrial markers indicated that there is a 2-2.5% divergence between the amphiatlantic populations of H. carunculata, confirming our expectations.…”
Section: Discussionsupporting
confidence: 89%
“…Almost all sequences were sequenced with the forward primer after preliminary sequencing with both primers yielding high-quality DNA traces. In the analysis, we included additional publicly available COI sequences from Ahrens et al (2013;KC017475-KC017594) and from Chatzigeorgiou et al (2014;KF878397-KF878476) to increase our geographic coverage. For example, in the Mediterranean COI data set, we have included our own sequences from Greece, as well as those sequences from Crete (Greece) from both Ahrens et al (2013) and Chatzigeorgiou et al (2014), and those from Malta (Ahrens et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Ahrens et al (2013) found no genetic differences between Hermodice carunculata populations of the Caribbean and the Eastern Atlantic and Mediterranean and placed Hermodice nigrolineata again into synonymy with Hermodice carunculata . The findings of Chatzigeorgiou et al (2014) concerning the phylogenetic relationships of the eastern Mediterranean populations of Hermodice carunculata support the results of Ahrens et al (2013).…”
Section: Checklistssupporting
confidence: 75%
“…The bearded fireworm is widely distributed in the Atlantic Ocean from the Caribbean to the Macaronesian islands, as well as in the Mediterranean and Red seas [20]. It is a voracious and generalist omnivorous species, preying mainly on anemones, gorgonians, and milleporid hydrocorals [31,32]. This species may pose public health risks if it becomes abundant off the Algarve coast, since its calcareous chaetae induce intense pain, inflammation, and edema when they come into contact with human skin.…”
Section: Discussionmentioning
confidence: 99%